PAPR Reduction of CC-OFDM MIMO Radar Waveform using Golay Codes - Kuswidiastuti, Devy; Suryani, Titiek; Prasetya, Alif Yudha (JAREE (Journal on Advanced Research in Electrical Engineering), 2024)
The development of modern radar technology demands multi-functional features that lead to the importance of designing a flexible, software-controlled digital waveform generator. The CC-OFDM MIMO radar waveforms allow flexibility in subcarrier management; hence it is possible to generate multiple narrow beams which transmitted simultaneously for providing all time coverage of the area.However, the main issue of OFDM is the high level of its PAPR value. This will cause non-linear distortion that potentially ruin the orthogonality of the OFDM subcarriers and in the end gives error in the radar detection results. In this paper, PAPR reduction using phase coding is done, by comparing the performance of complementary Hadamard, complementary Golay codes and combining it with Selective Mapping (SLM). The PAPR results show that complementary Golay codes without SLM are superior to complementary Hadamard with or without SLM. The maximum PAPR value of 65 beams transmitted simultaneously are 4.9 dB and 11.1 dB for CC OFDM waveform using complementary Golay codes and Hadamard respectively.